Red road to freedom : a history of the South African Communist Party, 1921-2021 - Lodge, Tom, 1951- (James Currey, an imprint of Boydell & Brewer Ltd, 2022)
"Lodge provides a richly detailed history of the Party's vicissitudes and victories; individuals - their ideas, attitudes and activities - are sensitively located within their context; the text provides a fascinating sociology of the South African left over time. Lodge is adept at making explicit what the key questions and issues are for different periods; and he answers these with analyses and conclusions that are judicious, clearly stated, and meticulously argued. Without doubt, this book will become a central text for students of communism in South Africa, of the Party's links with Russia and the socialist bloc, and of the Communist Party's changing relations with African nationalism - before, during and after three decades of exile."--! Back cover